IMPLEMENTASI MARKETING MIX TABUNGAN HAJI PADA PT. PANIN BANK SYARIAH, TBK CABANG MALANG - Early Ridho Kismawadi, Uun Dwi Al Muddatstsir Firda Azkiya Safitri Su?ud (JURNAL EKONOMI DAN BISNIS ISLAM, 2017)
This study develops an implementation issue marketing mix hajj savings on PT. Islamic Bank Panin Tbk, Malang Branch. This study by the increase in background backs hajj savings of 40% -60% in 2014-2015 and wanted to know about the application of the mar- keting mix in PT. Islamic Bank Panin Tbk, Malang Branch. The re- sult of this research is PT. Islamic Bank Panin Tbk branch Malang that all the marketing mix can already be applied properly by PT.  Bank Panin Tbk Syariah Branch Malang, but its implementa- tion must be adapted to target such people and places that will beaddressed and PT. Bank Panin Tbk Syariah Branch Malang pro- videsinnovations in its products to be in demand by customers   such as giving rewards to customers and marketing mix is applied to serve the activities provid- ed to customers.